Effects of Navier slip on film condensation heat transfer over upward facing horizontal flat surfaces with free edges. (December 2021) - Alsulami, Radi A.; Premnath, Kannan; Aljaghtham, Mutabe
Abstract: Transport phenomena involving condensate liquids generated from the phase-change heat transfer in microchannels and in engineered superhydrophobic surfaces require consideration of slip effects. Herein, the laminar film condensation over upward facing flat slabs and circular disks of finite sizes with free edges in the presence of wall slip effects is investigated. By considering the Navier slip model and extending the classical Nusselt analysis, the mass, momentum, and energy of the liquid film in two-dimensional/axisymmetric coordinates are solved for the film thickness and the heat transfer rate in non-dimensional form. Numerical solution yields the local structure of the condensate film profile and the Nusselt number for different values of slip coefficient. The results reveals that the condensate film on horizontal surfaces becomes thinner and the overall heat transfer rate is enhanced with an increase in the slip coefficient. In particular, an analysis of the results indicates a power law dependence of the Nusselt number on the non-dimensional slip coefficient with an exponent close to 0.5. Significant enhancement in phase change heat transfer follow from the modification of the local velocity profiles within the condensate film, resulting from the additional momentum gain near the wall surfaces due to increases in slip effects.